2014
DOI: 10.1016/j.cell.2013.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Premature Activation of the SLX4 Complex by Vpr Promotes G2/M Arrest and Escape from Innate Immune Sensing

Abstract: The HIV auxiliary protein Vpr potently blocks the cell cycle at the G2/M transition. Here, we show that G2/M arrest results from untimely activation of the structure-specific endonuclease (SSE) regulator SLX4 complex (SLX4com) by Vpr, a process that requires VPRBP-DDB1-CUL4 E3-ligase complex. Direct interaction of Vpr with SLX4 induced the recruitment of VPRBP and kinase-active PLK1, enhancing the cleavage of DNA by SLX4-associated MUS81-EME1 endonucleases. G2/M arrest-deficient Vpr alleles failed to interact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

20
282
5
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 194 publications
(309 citation statements)
references
References 62 publications
20
282
5
2
Order By: Relevance
“…Furthermore, the partial ability of the G2 arrest-defective Vpr S79A mutant to induce HLTF degradation suggests that a block in the cell cycle is not a prerequisite for the modulation of HLTF expression. Vpr triggers the degradation of the SLX4-associated Mus81 endonuclease, although conflicting results have been reported regarding the link between Vpr-mediated Mus81 degradation and G2 arrest (30,61). We confirmed that Vpr degrades both Mus81 and HLTF and that this degradation required DCAF1 (Fig.…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…Furthermore, the partial ability of the G2 arrest-defective Vpr S79A mutant to induce HLTF degradation suggests that a block in the cell cycle is not a prerequisite for the modulation of HLTF expression. Vpr triggers the degradation of the SLX4-associated Mus81 endonuclease, although conflicting results have been reported regarding the link between Vpr-mediated Mus81 degradation and G2 arrest (30,61). We confirmed that Vpr degrades both Mus81 and HLTF and that this degradation required DCAF1 (Fig.…”
Section: Resultssupporting
confidence: 75%
“…This hypothesis was attractive because both Vpr and depletion of some DNA translocases having apparent redundant function with HLTF interfere with SLX4com. For example, SWI/SNFrelated matrix-associated actin-dependent regulator of chromatin subfamily A-like protein 1 (SMARCAL1) was reported to interfere with MUS81 structure-specific endonuclease subunit (Mus81) or the SLX4 endonuclease complex and the repair of damaged replication forks (30,70,71). However, several lines of evidence suggest that HLTF is not involved in the cytostatic activity of Vpr.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In particular, Vpr was shown to directly bind SLX4 and was postulated to untimely activate the SLX4com via the CRL4-DCAF1 complex. These interactions were proposed to lead to aberrant DNA cleavage and cell cycle arrest (54). Additionally, MUS81 was reported to be down-regulated by Vpr, which was further confirmed by another two groups (55,56).…”
supporting
confidence: 50%